2013
DOI: 10.1111/den.12099
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of endoscopic submucosal dissection for early gastric cancer: A single‐center retrospective study

Abstract: ESD can be considered a standard treatment for EGC based on its expanded indications and low incidences of local recurrence and lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 25 publications
3
95
3
2
Order By: Relevance
“…However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study. Oda et al [12] also reported the favorable long-term outcomes of curative gastric ESD over follow-up periods of at least 5 years; however, they reported preliminary results of a multicenter questionnaire survey without collecting individual patient data, meaning that they could not estimate the long-term outcomes using the Kaplan-Meier method.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study. Oda et al [12] also reported the favorable long-term outcomes of curative gastric ESD over follow-up periods of at least 5 years; however, they reported preliminary results of a multicenter questionnaire survey without collecting individual patient data, meaning that they could not estimate the long-term outcomes using the Kaplan-Meier method.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, ESD has been performed to treat EGCs, including large and ulcerative lesions, and there have been a number of published reports on the short-and long-term outcomes of ESD for EGC [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanded indication lesions were associated with higher PPB in 1 study, 63 whereas PPB was not significantly different between standard and expanded indications in 3 studies despite a tendency for higher bleeding in the latter group. 48,64,65 Ulceration was not associated with PPB, 14 27 Submucosal fibrosis has also been analyzed and was not identified as an independent risk factor. 13,14,61,67 The presence of scarring was not identified as an influence on PPB in 3 studies, 32,51,58 although it was associated with higher PPB in 2 studies.…”
Section: Risk Factors For Post-esd Bleeding Risk Factormentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) is currently performed for early gastric cancer (EGC) with negligible risk of lymph node (LN) metastasis; the reported curative resection rates range from 73.6 to 94.7 % [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, cases of noncurative resection still exist because the precise endoscopic prediction of EGC in terms of tumor depth, lateral spread, or lymphovascular invasion is difficult before treatment [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%